ISSUES OF IMPROVING THE PROCEDURE FOR PREPARING A CRIMINAL CASE FOR TRIAL (World Bulletin of Management and Law, 2023)
This article is devoted to the theoretical problems of the stage of improving the meaning and procedure for using the expert opinion and expert testimony, which are one of the types of evidence when passing a lawful, reasonable and fair sentence in a criminal case. The significant influence of the expert's opinion on the author's judgment is noted, as well as the circumstances of the influence of the expert's opinion on the judgment are shown by practical examples and their analysis. For the court, including for the investigator, the inquirer and the prosecutor, due to the fact that no evidence has a pre-established force, the circumstances that must be revealed during the expert opinion through the evidentiary process are given. The expert's conclusion eliminates gaps and contradictions existing in the case, serves as confirmation of the arguments of individuals and (or) some testifying and refutation of others. Therefore, at the evidentiary stage, the courts not only evaluate the expert's opinion on the merits, which is the basis for sentencing, but also check the correctness of the assessments made by the investigative authorities on these evidences. Based on the provisions of the Criminal Procedure Code of the Republic of Uzbekistan, the range of main tasks of this stage, its specifics and the most important issues of the participants' procedural activities, as well as proposals for improving this stage are outlined.
Keywords: Criminal case; forensic expertise; expert opinion